Circulating cell-free DNA and tumor DNA dynamics in obstructive colon cancer undergoing neoadjuvant chemotherapy following stent placement - Zhang, Kunning; Han, Jiagang; Zhai, Zhiwei (Frontiers in Surgery, 2025)
BackgroundTo improve the prognosis of patients with obstructive colon cancer, performing neoadjuvant chemotherapy after self-expanding metallic stent (SEMS) placement followed by elective surgery is currently one of the treatment methods for obstructive colon cancer. However, the oncological risks of this treatment approach are currently unclear. To evaluate the oncological risks of this treatment model by detecting changes in circulating cell-free DNA (cfDNA) and circulating tumor DNA (ctDNA) during the stent placement combined with neoadjuvant chemotherapy process.MethodsFrom January to December 2023, 10 patients with obstructive colon cancer who received neoadjuvant chemotherapy after SEMS placement, followed by surgical treatment, were included in this study. Blood samples were collected one day before stent placement, 3 days after stent placement, one day before surgery, and one day after surgery. cfDNA and ctDNA in the blood were detected and analyzed.ResultsThe stent placement success rate was 100%, with no cases of perforation, displacement, or re-obstruction, and no perioperative deaths. After neoadjuvant chemotherapy, peripheral ctDNA decreased compared to before stent placement. There were no statistically significant differences in cfDNA and ctDNA changes at the four time points during the treatment process.ConclusionsThis study did not find an increase in ctDNA after stent placement combined with chemotherapy, suggesting that the model of stent placement combined with neoadjuvant chemotherapy for obstructive colon cancer may be a safe and reliable therapy.